Crossroad '86 - Hartman, Dave, (1986)
18 panels with some 50 photographs, size 62x70 cm or 62x55 cm, of plastic covered carton. Photo exhibition produced by Afrapix, Cape Town, South Africa on the destruction of the Crossroads complex and of KTC and the forced removal of the squatter communities in these townships of Cape Town in May-June 1986. All photographs in black-and-white and accompanied by short captions. Exposition used in information work by Holland Committee on Southern Africa (KZA).